Pharmacological Effects of Biosynthesis Silver Nanoparticles Utilizing Calotropis procera Leaf Extracts on Plasmodium berghei-Infected Liver in Experiment Mice - Murshed M; AL-Tamimi J; Mares MM; Hailan WAQ; Ibrahim KE; Al-Quraishy S (International Journal of Nanomedicine)
Mutee Murshed, Jameel AL-Tamimi, Mohammed M Mares, Waleed AQ Hailan, Khalid Elfaki Ibrahim, Saleh Al-Quraishy Department of Zoology, College of Science, King Saud University, Riyadh, 11451, Kingdom of Saudi ArabiaCorrespondence: Mutee Murshed, Email mmurshed@ksu.edu.sa; mutee@gmail.comIntroduction: Malaria caused by Plasmodium spp. is the most hazardous disease in the world. It is regarded as a life-threatening hematological disorder caused by parasites transferred to humans by the bite of Anopheles mosquitoes.Purpose: Calotropis procera leaf extract combined with biosynthesized silver nanoparticles (CPLEAgNPs) to evaluate its antiplasmodium and hepatoprotective effects against P. berghei-induced infection in experimental mice.Methods: The animal groups were divided into four groups: the first non-infected group was orally administered distilled water daily 7 days. The second group received an oral dose of 50 mg/kg of CPLE AgNPs. The third group received intraperitoneal injections of 105 P. berghei. The fourth group received of 105 P. berghei with 50 mg/kg CPLE AgNPs. All mice were anesthetized with CO2 and dissected for sample collection.Results: This study of C. procera leaves showed that they contain chemically active substances, as shown by the amounts of phenols, flavonoids, and tannins. The antioxidant activity of the samples was assessed using 1.1-diphenyl-2-picrylhydrazyl (DPPH) and 2.2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) assays. Treatment of infected mice with CPLE AgNPs for 7 days resulted in a significant decrease in parasitemia and a reduction in histopathological alterations in the liver. Furthermore, CPLE AgNPs mitigated oxidative damage caused by P. berghei infection in the liver. In addition, after receiving the medication, the liver levels of alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase decreased. In addition, CPLE AgNPs regulated the expression of liver cytokines, including IL-1β, and I-10.Discussion: Based on these findings, the study proved that CPLE AgNPs have hepatoprotective and antiplasmodial properties.Keywords: Plasmodium berghei, histopathological, antioxidant, oxidative, cytokine